Abnormal Liver Biochemistry Is Common in Pediatric Inflammatory Bowel Disease: Prevalence and Associations. Issue 12 (December 2015) - Valentino, Pamela L.; Feldman, Brian M.; Walters, Thomas D.; Griffiths, Anne M.; Ling, Simon C.; Pullenayegum, Eleanor M.; Kamath, Binita M.
Abstract : Background: Liver enzymes (LEs) abnormalities associated with pediatric inflammatory bowel diseases (IBD) are understudied. We undertook to describe the development and associations of abnormal LEs in pediatric IBD. Methods: We ascertained a cohort of 300 children with IBD and collected retrospective data. A Kaplan–Meier analysis determined the time to development of different thresholds of abnormal LEs. Associations between clinical variables and the development of abnormal LEs were determined. Results: The probability of developing the first episode of abnormal LEs above the upper limit of normal (ULN) within 150 months was 58.1% (16.3% by 1 mo post-IBD diagnosis). There was a 6% prevalence of primary sclerosing cholangitis (PSC) or autoimmune sclerosing cholangitis (ASC) in this cohort. Of those diagnosed with PSC/ASC, 93% had persistent LE elevations at a threshold of >2× ULN, while those without PSC/ASC had a 4% probability of this abnormality. Elevated gamma glutamyltranspeptidase levels of 252 U/L had a 99% sensitivity and 71% specificity for PSC/ASC in IBD. After exclusion of patients with PSC/ASC, corticosteroids, antibiotics, and exclusive enteral nutrition demonstrated strongly positive associations with the first development of abnormal LEs >ULN (hazard ratio 2.1 [95% confidence interval, 1.3–3.3], hazard ratio 5.6 [95% confidence interval, 3.6–8.9], hazard ratio 4.2 [95% confidence interval, 1.6–11.3], respectively). Conclusions: Abnormal LEs are common in pediatric IBD and occur early. PSC/ASC is associated with persistently high LEs and gamma glutamyltranspeptidase levels >252 U/L. Children with IBD are at risk of elevated LEs if they require medications other than 5-ASA to induce IBD remission. Abstract : Article first published online 13 August 2015.Supplemental Digital Content is Available in the Text.